The Notary Law Politics in the Notary Position Act - Agung Iriantoro (Jurnal Akta, 2022)
This study aims to determine the legal politics of the political aspects behind the process of forming laws and policies in a particular field, as well as greatly influencing the performance of relevant government institutions in that field in applying the provisions of legal products and policies, and also determine the policies of these institutions in a practical and operational setting. This research is a qualitative research with a normative juridical approach. Notary activities in Indonesia are heavily influenced by politics and law itself. The conclusion is that political influence can be seen from the making of a political product in the form of a special law that regulates the position of a notary, namely Act No. 2 of 2014 jo. No. 30 of 2004 concerning the Position of a Notary. And the status of Indonesia, which is a state of law, of course, will also affect the actions and actions of notaries because they must be guided by the applicable laws.